Crop establishment methods and Zn nutrition in Bt-cotton: Direct effects on system productivity, economic-efficiency and water-productivity in Bt-cotton-wheat cropping system and their residual effects on yield and Zn biofortification in wheat - PAUL, TARUN; RANA, D S; CHOUDHARY, ANIL K; DAS, T K; RAJPOOT, S K (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted at New Delhi (India) during kharif and rabi seasons of 2013–14 and 2014–15 to assess the performance of 2 crop establishment methods (CEMs) of Bt-cotton [Direct sowing and transplanting] and 5 zinc (Zn) levels [0, 2.5, 5, 7.5 kg Zn/ha through zinc sulphate hepta hydrate (ZSHH) and 0.5% ZnSO4 (ZSHH) foliar spray at 60 and 90 days after planting] applied to Bt-cotton on the system productivity, production–efficiency, economic–efficiency and water–productivity of Bt-cotton–wheat cropping system; as well as their residual effects on succeeding wheat in a Bt-cotton–wheat cropping system (CWCS) in a semi–arid Indo–Gangetic Plains Region (IGPR). In succeeding wheat, the residual effects of Zn levels applied to cotton were also compared with direct effect of Zn applied to wheat by replacing the foliar Zn spray treatment of cotton with Zn @ 5 kg/ha in wheat. The results revealed that direct and residual effects of cotton CEMs were non–significant on yield attributes and yield of wheat. However, the residual effects of Zn @ 5 and 7.5 kg/ha were significant on yield attributes and yield of wheat. Direct effect of Zn @ 5 kg/ha applied in wheat was at par with residual effects of 5 and 7.5 kg Zn/ha applied to cotton. In general, wheat grain yield was enhanced by 12.6, 12.3 and 12.9% during 2013–14, and 9.9, 8.1 and 8.3% during 2014–15 over control due to direct and residual effect of 2.5, 5 and 7.5 kg Zn/ha, respectively. Similarly on wheat straw yield. The influence of cotton CEMs on CWCS system productivity was non–significant. However, direct and residual effects of Zn levels induced a marked variation in CWCS system productivity as well as residual Zn fertility. Successive increase in Zn levels from 0 to 5 kg/ha in cotton resulted in significant increase in system productivity; thereafter, application of Zn @ 7.5 kg/ha revealed a non–significant influence. On an average, CWCS system productivity enhanced by 7.7% due to direct effect of 5 kg Zn/ha applied to wheat, and by 4.8, 10 and 9.9% due to residual effect of 2.5, 5 and 7.5 kg Zn/ ha over control. With successive increase in Zn–levels to cotton, a significant Zn–enrichment of wheat grain and straw was also observed. Cotton CEMs exhibited a significant influence on Zn content and uptake in wheat straw but with non-significant influence on wheat grains. Again, cotton CEMs exhibited a non–significant influence on system production–efficiency (PE), economic–efficiency (EE) and profitability. On the other hand, successive increase in Zn levels to cotton resulted in perceptible increase in system PE and EE up to 5 kg Zn/ha. Foliar Zn spray to cotton and direct Zn application to wheat also exhibited significant increase in system PE and EE over control, but, this treatment was at par with direct and residual effects of 5 and 7.5 kg Zn/ha. There was a significant influence of CEMs and Zn levels on water–use–efficiency (WUE) and water–productivity (WP) in CWCS. Residual effects of 5 and 7.5 kg Zn/ ha applied to cotton resulted in significantly higher net returns (NR) and benefit: cost ratio (BCR). Direct effect of 5 kg Zn/ha to wheat also exhibited higher NR and BCR in CWCS over control and residual effect of 2.5 kg Zn/ha. Overall, successive increase in Zn–levels led to significant enhancement in system productivity, PE, EE and water productivity up to 5 kg Zn/ha. The residual effects of 5 and 7.5 kg Zn/ha applied to Bt-cotton exhibited a significant influence on productivity, profitability and Zn biofortification of succeeding wheat which also remained at par with direct application of 5 kg Zn/ha applied to wheat in a Bt-cotton–wheat cropping system in a semi–arid IGPR.